市販生カキからのノロウイルスおよびA型肝炎ウイルスの検出 - 改田, 厚; 久保, 英幸; 綾田, 稔; 春木, 孝祐; 入谷, 展弘; 村上, 司; 勢戸, 祥介; 小倉, 壽; 西尾, 治 (SEIKATSU EISEI (Journal of Urban Living and Health Association), 2005)
During four seasons (2000/01, 2001/02, 2002/03 and 2003/04), a total of 157 samples of commercial raw oyster were examined for Norovirus (NV) and hepatitis A virus (HAV) using reverse transcription (RT)-PCR and real-time RT-PCR. Twenty-five samples (15.9%) were NV-positive. NVs were most frequently detected in oysters in January, with none detected in October and November. The highest incidence of NV-positive oysters and outbreaks of illness associated with ingestion of raw oysters was observed in the 2002/03 season. NVs detected in oysters were classified into four probe types (P1-A, P2-A, P2-B and 96065) and seven genotypes (one in genogroup I and six in genogroup II). HAVs, on the other hand, were detected in only two samples (1.3%) and the amount of HAV in the oyster was very low. The findings of the study suggested that commercial raw oysters contaminated with NVs were closely related with the occurrence of NV-outbreaks associated with the ingestion of oysters.